Proactive Repatriation and Justice-Seeking for Ancestors in Edinburgh University's "Skull Room" - Anderson, Nicole
Edinburgh University’s Anatomical Museum’s “Skull Room” holds the cranial remains of nearly 1800 individuals, stolen by phrenologists, anatomists and graduate students in the 19th and 20th centuries. This lecture reflects on a collaborative project of reparative justice that sought to reconnect First Nations and Inuit ancestors to their living descendants. It explores the importance of proactive repatriation and knowledge-sharing with descendant communities, the challenges of working with incomplete provenance, and the responsibilities inherent in bearing witness to colonial collections by researchers and academic institutions.